The Role of Ambivalent Sexism on Attitudes Towards Sexual Harassment: Study on Students in East Java - Rahayu, Ristanti Risqi; Herdiana, Ike (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
East Java is in second place after West Java as the province with the highest cases of gender-based violence against women in Indonesia. Society in general is more focused on severe forms of sexual violence, such as rape and sex trafficking, but less focused on their attitudes towards sexual harassment. Attitudes towards sexual harassment have an impact on victims, such as causing shame, disrupting individual well-being, and even leading to depression, both for those who experience it and those who witness it. One factor that is related to attitudes towards sexual harassment is ambivalent sexism. Ambivalent sexism is a form of hostility towards women while simultaneously feeling positive towards them but still in line with sexist antipathy. This research aims to empirically test the role of ambivalent sexism in attitudes towards sexual harassment among students in East Java. This research was conducted on 112 respondents with the criteria of students studying in East Java. Data were collected using the Ambivalent Sexism Inventory (ASI) and Sexual Harassment Attitude Scale (SHAS) questionnaires. Data collection was carried out by distributing online questionnaires. The data analysis technique used was a multiple linear regression test. The research results show that the two dimensions of ambivalent sexism, namely benevolent sexism and hostile sexism, have a significant role in attitudes towards sexual harassment. Benevolent sexism and hostile sexism each significantly predict attitudes towards sexual harassment. These results indicate that the higher the attitude towards traditional roles and stereotypes of women (benevolent sexism) accompanied by the need for sexual dominance, control, and viewing women as inferior (hostile sexism), the more tolerant attitudes towards sexual harassment will increase. Jawa Timur menempati posisi kedua setelah Jawa Barat sebagai provinsi dengan kasus kekerasan berbasis gender terhadap perempuan tertinggi di Indonesia. Masyarakat secara umum lebih fokus pada bentuk-bentuk kekerasan seksual yang parah, seperti pemerkosaan dan perdagangan seks, tetapi kurang fokus pada sikap mereka terhadap pelecehan seksual. Sikap terhadap pelecehan seksual memberikan dampak bagi para korban seperti menimbulkan rasa malu, mengganggu kesejahteraan individu, bahkan hingga berujung depresi, baik bagi yang mengalami maupun yang menyaksikannya. Salah satu faktor yang memiliki hubungan dengan sikap terhadap pelecehan seksual adalah ambivalent sexism. Ambivalent sexism adalah bentuk permusuhan terhadap perempuan sekaligus perasaan positif terhadap mereka tetapi masih sejalan dengan antipati seksis. Penelitian ini bertujuan untuk menguji secara empiris adanya peran ambivalent sexism pada sikap terhadap pelecehan seksual pada mahasiswa di Jawa Timur. Penelitian ini dilakukan pada 112 orang responden dengan kriteria mahasiswa/mahasiswi yang berkuliah di Jawa Timur. Pengambilan data menggunakan kuesioner Ambivalent Sexism Inventory (ASI) dan Sexual Harassment Attitude Scale (SHAS). Pengumpulan data dilakukan dengan menyebarkan kuesioner online. Teknik analisis data yang dilakukan adalah uji regresi linier berganda. Hasil penelitian menunjukkan bahwa kedua dimensi ambivalent sexism yaitu benevolent sexism dan hostile sexism memiliki peran yang signifikan pada sikap terhadap pelecehan seksual. Benevolent sexism dan hostile sexism masing-masing secara signifikan memprediksi munculnya sikap terhadap pelecehan seksual. Hasil ini menunjukkan bahwa semakin tinggi sikap terhadap peran tradisional dan stereotip perempuan (benevolent sexism) disertai dengan kebutuhan akan dominasi seksual, kontrol, dan memandang inferioritas perempuan (hostile sexism) akan meningkatkan sikap toleran terhadap pelecehan seksual.